Manganese Deficiency in Palms: ENH1015/EP267, 9/2005 - Broschat, Timothy K. (EDIS, 2019)
This document is ENH1015, one of a series of the Department of Environmental Horticulture, UF/IFAS Extension. Original publication date September 2005. ENH1015/EP267: Manganese Deficiency in Palms (ufl.edu)